Guru, Kesadaran Gender, dan Kepemimpinan Perempuan: Studi di Pondok Pesantren an-Najah, Muaro Jambi - Luluk Ambarwati (Prodi Bimbingan dan Konseling Islam (BPI) Fakultas Dakwah UIN Sulthan Thaha Saifuddin Jambi, 2022)
This research is motivated by the negative stigma of some people towards women and women's leadership. Therefore, this article will present gender awareness of teachers at An-Najah Islamic Boarding School, Muaro Jambi. More precisely, how is the understanding of the teachers in Islamic boarding schools towards women's leadership. This article applies the principles of field and library studies where the main data are obtained from interviews, observations, and documentation. This article concludes that the teacher at the An-Najah Sengeti Islamic Boarding School does not distinguish between a female leader. Then the attitude of the teacher shown under the leadership of women is that the teacher has an attitude that is quite independent, not confident, professional and can overcome existing problems. And the performance of teachers at An-Najah Islamic Boarding School can be categorized quite well in providing motivation and being able to communicate well. This can be proven by each teacher being able to carry out according to the program programmed at the An-Najah Sengeti Islamic Boarding School.